Incompleted gestational age as a risk factor for developmental disorder at 6 up to 36 months of age. - Pramudito, Pramudito (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: In developed countries, survival rate of preterm baby with gestational period more than 26 weeks has increased. Most studies on developmental outcomes were conducted on preterm baby with gestational period of less than 32 weeks. On the other hand, in developing countries the mortality rate of preterm baby with gestational period of less than 32 weeks is still high.Objective: To assess whether the incompleted gestational age is a risk factor for developmental disorder at 6 up to 36 months of age.Methods: Sixty four subjects born between 2001 April 1 to 2004 January 31 in Dr. Sardjito Hospital were enrolled, consisted of 31 children with incompleted gestational age (exposed group) and 33 children with completed gestational age (unexposed group). The developmental milestone was assessed using the DenverDeve/opmenta/ Screening Test/DDST (Denver //). Age line adjusment is used for exposed grou when the subject was born 4 weeks before completed gestational age and less than 3 years old.Results: There was no statistically significant diferrence on the prevalence of developmental, disorder at 6 to 36 months of age between exposed group and unexposed group in every area i.e. for gross motor: RR (95% Cl): 0,87 (0,24-3,19); language RR (95% Cl ): 1,48 (0,30-7,23 ) and personal social RR (95% Cl): 1,10 (0,10-17,83) or developmental conclusion: RR (95% Cl): 0,75 (0,23-2,48Conclusion: On the basis of developmental screening using DDST (Denver 11) incompleted gestational age (32-36) weeks was not a risk factor for developmental disorder at 6 to 36 months of age.Â Key words: incompleted gestational age - development disorder - Denver Developmental Screening Test/ DDST (Denver ll).